Sukow Ware at Vester Egesborg, Denmark? The Question of Import, Inspiration or Coincidence in Viking Age Pottery Style - Ulriksen, Jens Molter; Brorsson, Torbjörn (Danish Journal of Archaeology, 2023)
During archaeological excavations at Vester Egesborg, a landing site from the Late Germanic Iron Age and Viking Age was found. The find material at the site was large and varied, providing proof of contacts with other places in the southern Baltic Sea area. This includes a significant number of sherds looking like Early Slavic Sukow pottery, which suggests contacts between Slavs in Mecklenburg and the Scandinavian population in the Early Viking Age. It is difficult to distinguish between Sukow Ware and contemporary South Scandinavian pottery in terms of shape and fabric, but the relatively large portion of rim sherds looking like the Slavic pottery type in the ceramic assemblage from Vester Egesborg posed the question of whether Sukow Ware has been imported to the site. ICP-MA/ES analyses of a sample of ceramic sherds suggest the existence of a network including the regions of Scania, Holstein and Schleswig. Evidence for the production of Sukow Ware at Vester Egesborg or in southern Zealand cannot be provided unambiguously.